Chile's market share in the EU Market: The role of price competition in a panel analysis setting - Felicitas Nowak-Lehmann D.; Dierk Herzer; Sebastian Vollmer; Inmaculada Martínez-Zarzoso (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2006)
It is the objective of this paper to analyze Chile's development of market shares in the EU market in the period of 1988 to 2002, testing for the impact of price competitiveness on market shares with panel data. Price competitiveness is considered a decisive determinant of Chile's market shares since Chile's successful export products are rather homogeneous products (fish, fruit, beverages, ores, copper, and wood and products thereof). Six EU countries, namely France, Germany, Italy, the Netherlands, Spain and the UK, with perceptible imports from Chile in the above-mentioned sectors, serve as cross-sections in this study. It is found that Chile's market shares in all seven sectors under investigation were unstable in economic terms in the 1988-2002 period. From a statistical point of view market shares were non-stationary variables, integrated of order one (I(1)) and so were Chile's relatives prices and its competitors' relative prices, which turned out to be I(1), too. All variables being I(1), a panel cointegration test was conducted. Pedroni's residual based cointegration test revealed cointegration between market shares and relative prices in all seven sectors allowing regression coefficients to be estimated by means of Dynamic Ordinary Least Squares (DOLS). The DOLS results were then compared with the ones obtained by the Three Stage Feasible Generalized Least Squares (3SFGLS) and the Generalized Method of Moments (GMM) technique.
Keywords: F14; F17; C23; 330; Preiswettbewerb; Internationale Marktsegmentierung; Internationale Wirtschaftsbeziehungen; Chile; EU-Staaten